The effect of research method type on stereotypes' content: A brief research report. Issue 3 (4th May 2018) - David, Daniel; Bizo, Aurelian; Cimpean, Alina Ioana; Oltean, Horea; Cardos, Roxana; Soflau, Radu; Negut, Alexandra
ABSTRACT: Stereotype Content Model (SCM) emphasizes the content rather than the underlying processes of the stereotypes and the content might be influenced by several cultural dimensions (e.g., individualism vs. collectivism). The main dimensions of SCM—namely warmth and competence —underlying various contents are assumed to be universal. However, from a cognitive science paradigm, we argue that different research methods (i.e., data collections and data analysis) might also yield different stereotype contents that might impact the universality versus specificity problem in the SCM. Indeed, using a sample from a collectivistic country (i.e., Romania), we found that using different methods in data collection (i.e., unstructured vs. semi-structured vs. structured interview) and different methods of data analysis (i.e., availability vs. accessibility scores) might be an important research strategy to counter artefacts and confusions in the universality versus specificity problem related to the SCM. Theoretical and practical implications are discussed.